Toxic Anterior Segment Syndrome after Foldable Artiflex Iris-Fixated Phakic Intraocular Lens Implantation - Lucien A. M. van Philips (Journal of Ophthalmology)
Toxic anterior segment syndrome (TASS) developed in four cases after uneventful implantation of a foldable iris-fixated phakic intraocular lens (pIOL). Two cases occurred sequentially in one patient. The TASS subsided without complications in all cases after intensive topical steroid treatment. A multitude of possible causes is considered for the occurrence of these TASS cases. From the sterilization and cleaning of surgical instruments to the possibility of endotoxines in ophthalmic viscosurgical devices (OVD). These rare cases should alert the surgeon to the possibility of TASS after pIOL implantation.